Analisa Sense of Place Kampung Wae Rebo untuk Pengembangan Wisata di Manggarai - Dwiputri, Marianne Tunggadewi Juluk (Universitas Ciputra Surabaya, 2021)
Kampung Wae Rebo is the traditional village of Manggarai and is the only village in Manggarai that still maintains the village pattern and architecture of the traditional Manggarai buildings. This village has historical, cultural, architectural and unique character values ​​so that it becomes a destination for local tourist and foreign tourists. This village has a sense of place which is formed by physical and non-physical elements that influence tourist with unique experiences and perceptions. The research objective was to find out the elements that makes the sense of place of Wae Rebo village which play a role in providing human experience and sensory perceptions of physical elements in describing the sense of place of Wae Rebo village so that it can be a reference for the development of tourist objects in Manggarai. The method used in this study is a qualitative method by conducting case studies, interviews and in-depth observations in the village of Wae Rebo and its surroundings. From the results of this study, it was obtained several physical and non-physical elements that formed a sense of place in Wae Rebo village, including: access to achievements, landscapes, historical, social and architectural aspects of buildings, etc.